Sustainable power generation for at least one month from ambient humidity using unique nanofluidic diode - Zhang, Yong; Yang, Tingting; Shang, Kedong; Guo, Fengmei; Shang, Yuanyuan; Chang, Shulong; Cui, Licong; Lu, Xulei; Jiang, Zhongbao; Zhou, Jian; Fu, Chunqiao; He, Qi-Chang (Nature communications, 2022)
The continuous energy-harvesting in moisture environment is attractive for the development of clean energy source. Controlling the transport of ionized mobile charge in intelligent nanoporous membrane systems is a promising strategy to develop the moisture-enabled electric generator. However, existing designs still suffer from low output power density. Moreover, these devices can only produce short-term (mostly a few seconds or a few hours, rarely for a few days) voltage and current output in the ambient environment. Here, we show an ionic diode–type hybrid membrane capable of continuously generating energy in the ambient environment. The built-in electric field of the nanofluidic diode-type PN junction helps the selective ions separation and the steady-state one-way ion charge transfer. This directional ion migration is further converted to electron transportation at the surface of electrodes via oxidation-reduction reaction and charge adsorption, thus resulting in a continuous voltage and current with high energy conversion efficiency. Energy harvesting of humidity present in air can be used for the development of clean energy sources and self-sustained systems. The authors propose a nanofluid energy conversion system with integrated ionic diode-type hybrid membrane for energy generation in environmental moisture.